Structural performances of pultruded GFRP emergency structures – Part 1: Experimental characterization of materials and substructure. (15th April 2019) - Cavaleri, L.; Di Paola, M.; Ferrotto, M.F.; Scalici, T.; Valenza, A.
Abstract: This paper presents an experimental study in the field of structures made of pultruded fiber reinforced polymers (FRP) elements to be used for emergency purposes. A preliminary design of a 3D pultruded glass fiber reinforced polymer structure is presented with the mechanical characterization of the constituting elements. The axial and flexural properties of laminate and I-shaped GRFP profiles are discussed considering the short term creep. In a companion paper, the benefits, the limits and the reliability of the structure analyzed for emergency applications are discussed. In details, the numerical structural analysis of the full-scale 3D model is described followed by the experimental assessment of the structural capacity by a full-scale 2D model.